2022
DOI: 10.1097/gox.0000000000004374
|View full text |Cite
|
Sign up to set email alerts
|

Hemodynamics and Vascular Histology of Keloid Tissues and Anatomy of Nearby Blood Vessels

Abstract: Background: Keloids are red‚ invasive scars that are driven by chronic inflammation in the reticular dermis. The role of blood vessels in keloid behavior remains poorly understood. In the present study with 32 keloid patients, we examined the hemodynamics of keloid tissue, the anatomy of the blood vessels feeding and draining the keloids, and the vascular histology of keloids. Methods: Ten patients with large anterior chest keloids underwent near-infrared spectroscopy, which measured regional saturation of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 18 publications
1
6
0
Order By: Relevance
“…Initially, using CD31 as a marker for vasculature, we compared the vasculature area between the leading edge and the center of keloids. The average vasculature area was found to be 10% in the leading edge and 3% in the keloid center, confirming the previously reported (53) higher vasculature density at the leading edge of keloids compared to the center (Figure 3B). Subsequently, employing PDGFRA as a pan-fibroblast marker (18), we compared the proportion of CD74 + fibroblasts, identified as cells double-positive for PDGFRA and CD74 staining, between the leading edge and the center of keloids.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…Initially, using CD31 as a marker for vasculature, we compared the vasculature area between the leading edge and the center of keloids. The average vasculature area was found to be 10% in the leading edge and 3% in the keloid center, confirming the previously reported (53) higher vasculature density at the leading edge of keloids compared to the center (Figure 3B). Subsequently, employing PDGFRA as a pan-fibroblast marker (18), we compared the proportion of CD74 + fibroblasts, identified as cells double-positive for PDGFRA and CD74 staining, between the leading edge and the center of keloids.…”
Section: Resultssupporting
confidence: 90%
“…The fibro-proliferative and invasive nature of keloids necessitates a robust angiogenic mechanism at its command to transport oxygen and nutrients. Indeed, enhanced neo-vascularization activities of endothelial cells (53) as well as fibroblasts with stronger pro-angiogenic secretory phenotypes (33) were observed at the leading edge of keloids compared to keloid centers. The standard-of-care treatment modalities for keloids, including surgical excision, compression dressings, laser therapy, radiation, corticosteroids, and cytotoxic drugs, offer only limited efficacy with a high risk of recurrence (63).…”
Section: Discussionmentioning
confidence: 99%
“…14 This study suggests a significant relationship between the site of keloid and dermal vascularization, whereas vascularization was more common at the edge of the lesion, as this site has more robust neovascularization compared to the center of the keloid lesion, which tends to have fewer vessels, leading to ischemia. 13,19 Most of our study subjects had keloids on their ears and chests with vascularization features on histopathological examination. Another study by Matsumoto revealed that there is an increase in vascularization surrounded by collagen hyalinization in the papillary dermis of ear keloids.…”
Section: Discussionmentioning
confidence: 99%
“…12 The formation of neovascularization, along with an increase in inflammatory cells, is the effect of mechanical stimulation on body areas with high tension. 13 Ogawa hypothesized that keloids result from an exaggerated inflammatory response by a strong mechanical stimulus in high-tension areas. 14 Histopathological features of keloids include thickened epidermis as well as vascularization and infiltration of inflammatory cells in dermis.…”
Section: Introductionmentioning
confidence: 99%
“…Keloids are characterized by the excessive deposition of collagen during abnormal wound healing [ 1 ], which leads to a fibroproliferative inflammatory response with neovascularization at the leading edge [ 2 ]. Life quality of keloid patients is dramatically affected by physical symptoms, including pruritus and pain, as well as psychological barriers [ 3 ].…”
Section: Introductionmentioning
confidence: 99%